2000
DOI: 10.1074/jbc.275.7.4734
|View full text |Cite
|
Sign up to set email alerts
|

The Monoclonal Antibody 1F6 Identifies a pH-dependent Conformational Change in the Hydrophilic NH2 Terminus of NhaA Na+/H+ Antiporter ofEscherichia coli

Abstract: One of the most interesting properties of the NhaA Na ؉ /H ؉ antiporter of Escherichia coli is the strong regulation of its activity by pH. This regulation is accompanied by a conformational change that can be probed by digestion with trypsin and involves the hydrophilic loop connecting the transmembrane helices VIII-IX. In the present work we show that a monoclonal antibody (mAb), 1F6, recognizes yet another domain of NhaA in a pH-dependent manner. This antibody binds NhaA at pH 8.5 but not at pH 4.5, whereas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
47
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 28 publications
1
47
0
Order By: Relevance
“…In the present work, we have identified a novel mutation, E252C in loop VIII-IX, that has a very drastic effect on the pH response of NhaA. Whereas other mutations in this loop (E241C and V254C (19)) and other loops (15,18) cause acidic shift in the pH dependence of the activity of NhaA, Cys replacement mutation E252C causes an alkaline shift of one pH unit. As yet, such an alkaline shift of the pH response of NhaA has previously been found only in mutations at position 127 in the middle of TMS IV (21).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…In the present work, we have identified a novel mutation, E252C in loop VIII-IX, that has a very drastic effect on the pH response of NhaA. Whereas other mutations in this loop (E241C and V254C (19)) and other loops (15,18) cause acidic shift in the pH dependence of the activity of NhaA, Cys replacement mutation E252C causes an alkaline shift of one pH unit. As yet, such an alkaline shift of the pH response of NhaA has previously been found only in mutations at position 127 in the middle of TMS IV (21).…”
Section: Discussionmentioning
confidence: 90%
“…Monoclonal antibody 1F6 raised against the NhaA antiporter (17) identified that the N terminus of NhaA, its epitope, responds to pH (18). The antibody binds NhaA at pH 8.5 but not at pH 4.5.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments on cleaved NhaA allowed assign one class to pulling from the Cterminal end and the other one to pulling from the N-terminal end. However, the analysis also showed that the majority of unfolding events reflected pulling the C-terminal end of NhaA; an effect, which may be explained by the different accessibility of both terminal ends to the AFM stylus (Venturi et al 2000).…”
Section: Probing Molecular Interactions Of Single Membrane Proteinsmentioning
confidence: 95%
“…Another example concerns the biochemistry of NhaA, a bacterial Na ϩ /H ϩ antiporter that is strongly regulated by pH (6). A specific mAb was shown able to bind only the alkaline pH state of NhaA (7), and eptiope mapping disclosed a previously unpredicted conformational change upon activation (8).…”
mentioning
confidence: 99%